The war that saved my life - Bradley, Kimberly Brubaker (Puffin Books, an imprint of Penguin Random House LLC, 2015)
A young disabled girl and her brother are evacuated from London to the English countryside during World War II, where they find life to be much sweeter away from their abusive mother.
Keywords: World War, 1939-1945 -- Evacuation of civilians -- Great Britain -- Juvenile fiction; World War, 1939-1945 -- Evacuation of civilians -- Fiction; People with disabilities -- Fiction; Brothers and sisters -- Fiction; Great Britain -- History -- George VI, 1936-1952 -- Fiction